913 An Audit of Colonoscopy Compliance Within A Screening Programme for Patients with A Family History of Colorectal Cancer (CRC). (4th May 2021) - Abbakar, M; Boxall, P; James, T; Lim, M
Abstract: Introduction: Guidelines on the management of hereditary CRC were updated in 2019 and have led to more stringent use of surveillance colonoscopies. Patients with 'family history' (FH) CRC Surveillance programme at York Hospitals Trust were studied to assess compliance with colonoscopy recommendations. Method: Current BSG/ACPGBI guidelines recommend biennial, quinquennial, one-off or no colonoscopy surveillance for patients with Lynch syndrome, and those deemed to have high, moderate, and average risks of developing hereditary cancer, respectively. Examination of electronic records and clinical notes were performed to determine if they were Lynch positive and/or if they could be assigned a risk category. Results: Database of 227 patients, of which 14 were high, 61 moderate and 45 were low risk. 47 had Lynch syndrome. Compliance of colonoscopy was poor for patients with average and moderate FH risk (both 0%). Compliance was higher for patients with high risk of FH (50%) and those with Lynch syndrome (57%) Risk was indeterminate in 24 patients due to inadequate data therefore compliance could not be assessed. Conclusions: A large proportion of patients with low to moderate 'FH' risk within our current surveillance programme had unnecessary colonoscopies. Stratification of patients into the appropriate risk categories optimizes the benefit from surveillance programmes.